2006
DOI: 10.1177/021849230601400310
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Bilateral Bronchiectases: Results in 29 Patients

Abstract: Bronchiectasis is a major cause of morbidity and mortality in developing countries. Staged bilateral segmental resection of the lungs is performed in selected patients. Our experience of surgical removal of 87 bilateral bronchiectases in 29 patients during an 11-year period was reviewed retrospectively. High-resolution computed tomography was performed preoperatively in all patients to locate the anatomic sites of bronchiectasis. The mortality and morbidity of the surgical procedure, clinical symptoms, age dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…Maziéres et al [36] observed that a total disappearance or regression of preoperative symptoms occurred in 75% of such patients. In a recent study [38], the authors suggest that surgery for bilateral NCFB can be performed with morbidity and mortality patterns quite similar to those results in localized disease, with a disappearance or regression of preoperative symptoms in 83% of patients.…”
Section: Antimicrobial Therapymentioning
confidence: 68%
“…Maziéres et al [36] observed that a total disappearance or regression of preoperative symptoms occurred in 75% of such patients. In a recent study [38], the authors suggest that surgery for bilateral NCFB can be performed with morbidity and mortality patterns quite similar to those results in localized disease, with a disappearance or regression of preoperative symptoms in 83% of patients.…”
Section: Antimicrobial Therapymentioning
confidence: 68%
“…Besides medical treatment and respiratory physiotherapy, surgical treatment is an eligible therapy for patients with non-CF bronchiectasis, especially to those with little response to conservative interventions 7 . Over the years, many studies have reported surgical intervention in the management of patients with non-CF bronchiectasis 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 . The surgical procedure was aimed at primary resection of the affected area, as assessed by high-resolution computed tomographic (HRCT).…”
mentioning
confidence: 99%
“…Extrapleural dissection is preferred to avoid spillage of lung content into pleural space. After identification of the hilar structures and opening of the major fissure, arterial, venous, and bronchial branches are isolated and divided, respectively [39,63].…”
Section: Surgical Procedures 51 Thoracotomymentioning
confidence: 99%
“…The reported rates of perioperative mortality ranged from 0.41% [23] to 8.3% [25]. The causes of early mortality in literature include: respiratory failure [2,27,28,41,49,57], intraoperative bleeding [24,28,46], postoperative pneumonia [25,37], empyema [25,32], pulmonary edema [27,46], cardiac-related causes including myocardial infarction or arrhythmia [27,35,47,49,58], speptic shock [27,56], gastrointestinal bleeding due to sepsis and stress ulcer [39], uncontrolled hemoptysis [27], pulmonary embolism [22,32,48,58], cardiac arrest in patients with Kartagener syndrome [36], disseminated intravascular coagulation [44], nephropathy [22], downstream consequences of bronchial stump fistula [48,60], multiple organ failure [48,60], and causes unrelated to disease or technique such as cerebral edema in a child due to previously undiagnosed aquaeductus stenosis and hydrocephalus [24]. The disease-related consequences which indirectly attribute to early death include: severe disease requiring pneumonectomy or completion [28,58], massive bleeding during the operation because of dense ad...…”
Section: Postoperative Outcomes Of Lung Resection 61 Mortalitymentioning
confidence: 99%
See 1 more Smart Citation